GENDER SPECIFICS OF THE RISK FACTORS AND RELATION WITH MYOCARDIAL INFARCTION IN PATIENTS OF VARIOUS AGE GROUPS - Suspitsina, I. N.; Sukmanova, I. A. (Kardiovaskuli͡a︡rnai͡a︡ terapii͡a︡ i profilaktika, 2016)
Aim. To study gender specifics of risk factors and to assess their relation with myocardial infarction development (MI) in patients of various age subgroups. Material and methods. Totally, we included 188 men and women with Qand non-Q MI at the age 45-74 y.o., selected to 4 groups depending on age and gender. For all patients we evaluated clinical and anamnestic data, lipid profile, carbohydrate metabolism markers, sex hormones, C-reactive protein; we assessed hypodynamia level, depression and anxiety using questionnaires. To findout a relation of risk factors (RF) with MI development, statistically, we invented mathematical models of assessment of odds ratio for non-fatal MI cases for male and female population of patients.Results. For the assessed males the most significant risk factors were smoking, lipid disorders, overweight; for older males additionally RF were carbohydrate metabolism disorders with insulin resistance development, and mostly abdominal obesity. For women, main RF were carbohydrate metabolism disorders due to 2 type diabetes, arterial hypertension, obesity with its abdominal type, and lipid disorders.Conclusion. The invented mathematical models of evaluation of odds ratios make it to estimate the probability of non-fatal MI in men and women using their age and collection of RF.